Implementasi Standar Pelayanan Kebidanan pada Masa Nifas di Puskesmas - Bekti Yuniyanti; Mundarti Mundarti; Arfiana Arfiana (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2024)
Midwife service standards are stated in Minister of Health Regulation No. 28 of 2017 and Minister of Health Regulation No. 21 of 2021, the authority of midwives during the postpartum and breastfeeding period includes providing Vitamin A, IMD guidance and promotion of exclusive breastfeeding, and counseling, preventing psychological disorders, as well as postnatal family planning support. carried out through KF I-IV. The research aimed to describe the implementation of midwifery service standards during the postpartum period by midwives at the Community Health Center. This type of research used a quantitative descriptive study, a sample of 48 midwives, conducted in October 2023. The results of the research at KF I found that 85.4% gave vitamin A capsules, 87.5% asked about anxiety. KF II was found to give vitamin A 20.8%, Asking about anxiety/sadness 83%, Givi ng advice on sports activities 64.5%, Advice on baby care at home 91.7%, Advice on exclusive breastfeeding 89.6%, Advice on nutrition 91.7%. KF III Providing vitamin A 16.7%, Asking about anxiety/sadness 77.1%, Ensuring exclusive breastfeeding 77.1%. KF IV 97.9% of midwives always provide all services.